Comparative Analysis of the Effect of Low-Frequency Repeated Transcranial Magnetic Stimulation and Extracorporeal Shock Wave on Improving the Spasm of Flexor after Stroke. (24th August 2021) - Xu, Dandan; Cao, Haiyan; Fan, Yingjie; Yan, Dongmei; Su, Min
Abstract : Poststroke spasticity (PSS) patients with muscle spasticity are effectively relieved by low-frequency repetitive transcranial magnetic stimulation (rTMS) or extracorporeal shock wave treatment (ESWT). However, there are relatively few reports about the difference in the efficacy of rTMS and ESWT for PSS. In this study, we examined and recorded the levels of UE motor section of the Fugl–Meyer Motor Assessment Scale (FMA-UE), myoelectric signal time-domain range integral values (iEMG), Modified Ashworth Scale (MAS), and Modified Barthel Index (MBI) before and after treatment to observe the differences in treatment effects between rTMS and ESWT in patients with PSS. 66 patients with PSS were enrolled in the study and signed an informed consent form, and the study was approved by the Ethics Committee of the First Hospital of Soochow University (2019008). The patients were divided into rTMS group, ESWT group, and regular group according to the random number table method, and there were 22 patients in each group. The rTMS group and ESWT group were treated with rTMS and ESWT on the basis of conventional treatment in the regular group, 5 times a week, and the total treatment time was 4 weeks. The results of the study showed that iEMG, MAS, FMA-UE, and MBI scores in the rTMS, ESWT, and regular groups were significantly ameliorated after treatment compared with those before treatment. The efficacy of the ESWT group was significantly better than in the regular group and slightly better than in the rTMS group, as shown by the iEMG, MAS, FMA-UE, and MBI scores, and the iEMG score of the ESWT group was significantly better than the rTMS group, while there were no significant differences in other indexes. The FMA-UE and MBI scores in the rTMS group were significantly better than those in the regular group after treatment in the rTMS group; however, the comparison between iEMG and MAS scores was not statistically significant. It can be seen that both rTMS and ESWT can alleviate upper limb flexor spasm, improve upper limb motor function, and improve activities of daily living in patients with PSS. Among them, ESWT has better antispasmodic effect and better short-term treatment effect.